Furrow Diking as a Mid‐Southern USA Irrigation Strategy: Soybean Grain Yield, Irrigation Water Use Efficiency, and Net Returns above Furrow Diking Costs. Issue 1 (11th April 2019) - Bryant, C. J.; Krutz, L. J.; Nuti, R. C.; Truman, C. C.; Locke, M. A.; Falconer, L.; Atwill, R. L.; Wood, C. W.; Spencer, G. D.
Abstract : Core Ideas: Furrow diking increases soybean irrigation water use efficiency. Furrow diking should be a Mid‐Southern USA BMP. Furrow diking reduces Mississippi River Valley Alluvial Aquifer overdrafts. Best management practices (BMP) to improve irrigation efficiency and rainfall capture are needed in the Mid‐Southern USA to ease overdrafts from the Mississippi River Valley Alluvial Aquifer (MRVAA). One potential BMP is furrow diking (FD), wherein tillage is used to create small basins within the furrow to capture water from rainfall and irrigation. The objective of this research was to quantify the effect of FD on soybean grain yield, IWUE, and economic analysis under both irrigated and rainfed environments. Two studies were conducted to evaluate FD in irrigated and rainfed systems. Treatments included FD and non‐diked (control) in a randomized complete block design with six replications. Furrow diking had no impact on soybean grain yield in either irrigated or rainfed environments ( P > 0.05). Similar yields were maintained in the FD system when 25% less water was applied, increasing the irrigation water use efficiency by 28% ( P < 0.0001). No effect of FD was observed on total revenue or net returns above FD costs ( P > 0.05). These data indicate FD is a possible BMP for increasing irrigation efficiency and decreasing aquifer withdrawals in Mid‐Southern USA soybean production.